Metodologia de análise e adequação da rede de distribuição quanto às violações de tensão - Vilela Júnior, Wagner Alves (2022)
This paper proposes a computational process development capable of filling the electric power sector shortage regarding voltage non-conformities identification in electric power distribution network accounting for loads dynamic behavior at medium and low voltages. The methodology compares regulatory requirements and makes available in software some possible actions in an attempt to adjust voltage levels, avoiding inconvenience and penalties for energy utilities providers. The method involves a data extractor construction for electricity provider company’s databases, computer simulations and comparison of obtained results with values established in electricity quality control standards. Thus, finding non-conformity locations and determining network adjustments to correct tension indexes in permanent regulation. The proposal features a reduction in electricity utilities operating costs, increasing efficiency in operation and energy quality available to consumers.